Carbon quantum dots functionalized tapered optical fiber for highly sensitive and specific detection of Leptospira DNA. (January 2023) - Zainuddin, Nurul Hida; Chee, Hui Yee; Rashid, Suraya Abdul; Ahmad, Muhammad Zamharir; Bakar, Muhammad Hafiz Abu; Mahdi, Mohd Adzir; Yaacob, Mohd Hanif
Graphical abstract: Highlights: An infectious disease called leptospirosis has caused human mortality, alarming health professionals. This biosensor acts as an alternate leptospirosis diagnostic tool by using tapered optical fiber as a sensing transducer. Leptospira DNA detection was enhanced by functionalizing tapered optical fibre with carbon quantum dots (CQDs). This article suggests the development of a more sensitive, specific, and reliable leptospirosis diagnostic tool. Abstract: In this paper, we report on the development of DNA biosensor using carbon quantum dots (CQDs) to enhance Leptospira DNA detection. Leptospira is a bacterium that invades human body and cause leptospirosis disease. Leptospirosis has attracted attention mainly due to several cases of human mortality which have distressed health professionals. This biosensor system employs tapered optical fiber as a sensing transducer. The CQDs were functionalized at the tapered region via in situ deposition (drop-casted) before incubation using commercialized chemicals to link the 16 s ribosomal RNA gene (rrs) probe DNA. Detection was achieved with the occurrence of hybridization between the probe DNA and different concentrations of complementary DNA ( Leptospira DNA). This biosensor with limit of detection (LOD) of 1.0 fM demonstrated better sensitivity at 1.8295 nm/nM and higher affinity as its dissociation constant (Kd ) of 0.552 × 10 −09 M is lower compared to previous reported biosensors without CQDs. High specificity biosensor is validated when minimal shift was observed for non-complementary DNA. This novel biosensor was also able to distinguish between genomic DNA of Leptospira serovars and Clostridium difficile as control sample. The proposed biosensor has successfully exhibited the prominent role of nanomaterial for sensor enhancement. Consequently, the biosensor approach in this study has emphasized the potential for the development of more sensitive and reliable leptospirosis diagnostic testing in the future.